Traditional Chinese medicine (TCM) massage for the treatment of congenital muscular torticollis (CMT) in infants and children: A systematic review and meta-analysis. (May 2020) - Chen, Shu-Cheng; Ho, Yuen-Shan; Kwai-Ping Suen, Lorna; Yu, Juan; Tang, Wei; Jiang, Jin-Feng; Qu, Xiao-Yong; Yeung, Wing-Fai
Abstract: Background and purpose: Congenital muscular torticollis (CMT) is a musculoskeletal condition occurring in infants and children. This systematic review is conducted to summarize the current evidence on the effects and safety of TCM massage therapy for the treatment of CMT in infants and children. Methods: We searched for randomized controlled trials (RCTs) and quasi-RCTs on TCM massage for CMT in PubMed, Embase, CENTRAL, CINAHL, AMED, PsycINFO, Ovid MEDLINE, TCMLARS, ICTRP, CSTJ, CNKI, Wanfang Data, CBM, Taiwan Electronic Periodical Services, and the Index to Taiwan Periodical Literature System. Two reviewers conducted the data collection and analysis separately. Cochrane's collaboration tool was used to assess the risk of bias, and GRADEpro was used to assess the overall quality of the evidence. RevMan 5.3 software was used for data analysis with a random-effect model. Results: A systematic review of six RCTs and one quasi-RCT was conducted with a meta-analysis of two of the RCTs. Pooled analysis showed that TCM massage has similar effects to those of stretching therapy on CMT symptoms in terms of effective rate (risk ratio: 1.00, 95% CI: 0.94–1.06; I 2 = 0%; P = 0.99). Conclusion: Evidence suggests that TCM massage therapy is beneficial for treating CMT in infants and children. Further clinical trials with high-quality methodologies need to be conducted. Highlights: TCM massage therapy appeared to be superior to neck splint correction therapy for CMT. TCM massage therapy seems to have stronger effects as an adjunct intervention for CMT. Both TCM massage and stretching resulted in overall improvements as measured by the effective rate. TCM massage therapy might be beneficial for CMT in infants and children.